STUDI PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI KECAMATAN MALINAU BARAT KABUPATEN MALINAU - Denny Andreas (Jurnal Paradigma (JP), 2017)
This Research aim is to determine to what extent does motivation influence the  achievement of employees working in the Office of Public Works Malinau District of North Borneo. The results of the study concluded that the hypothesis of this study that states that the motivation variables include physiological needs, safety needs, social needs, esteem needs and self-actualization needs This hypothesis stating that the requirements of Safety is a motivational variable that has the most dominant influence on the performance of employees in the office of the Public Works Department Malinau District of North Borneo was convicted in the amount of 25.3%, while the smallest variable effects on work performance is variable social needs, amounting to 01.8%.